Mengelola Emosi Remaja di Tengah Konflik Sosial - alifia, rahillah (Maliki Interdisciplinary Journal, 2026)
Adolescence is a challenging developmental stage and prone to social conflict. Volatile adolescent emotions can trigger explosive, aggressive, or withdrawn behavior, leading to prolonged conflict. Good emotional regulation plays a crucial role in preventing aggressive behavior and enhancing emotional resilience in adolescents. Adolescent emotional regulation is influenced by internal factors, including mindset, emotional intelligence, and self-awareness, as well as external factors such as family parenting styles, social support, and the campus environment. Positive emotions and environmental support can enhance adolescents' emotional resilience to social stress. Families, schools, and social environments need to systematically implement adolescent emotion management to develop resilient and socially mature adolescents. Practical strategies include assertive communication, emotional pauses, and self-reflection, among others, which help adolescents better manage their emotions. This enables them to navigate social conflict more wisely and enhance their psychological well-being. Furthermore, family and social environments play a fundamental role in supporting adolescents' emotional regulation. Parents and families should foster warm and supportive communication so that adolescents feel free and comfortable to open up. Campuses should provide an educational environment free from bullying and supportive of adolescents' social and emotional development. Society must support the creation of a more youth-friendly social environment.